Kampung Ku in the City Series I / Wan Zamani Wan Zakaria - Wan Zakaria, Wan Zamani (Faculty of Art and Design, 2021)
Kampung Ku in the City Series I is a constructed image manipulation combined with illustrative abstract art in digital composition that visualizes the story of Kampung Ku series. The word kampung also refers to a settlement or compound of a certain ethnic community, which later become the names of places. Many people understood that a kampung is located merely in rural areas far away from the city but for some who live and were born in the city, the term applies to enclosed development and neighbourhoods within towns and cities. This artwork reveals the concept of settlement in the city that features historical building type of communal structure addressing colour behaviour, element of acts and traditions which are associated with kampung with chicken seen in the middle of the modern metropolis.